Diagnostic challenge between Crohn's disease and intestinal tuberculosis in chronic diarrhea with ulcerated jejunal stenosis: a case report - Costa-Barney, Valeria (2020)
Intestinal tuberculosis and Crohn's disease are a diagnostic challenge because of the clinical, radiological and endoscopic similarity. The histological and microbiological findings are positive in less than 50%, which delays the correct treatment, putting the patient at risk. We reported a 34-year-old immunocompetent patient with 4 years of malabsorptive diarrhea, weight loss, nocturnal diaphoresis, abdominal pain and an ulcer with stenosis in the jejunum was found; she mpirical antituberculosis treatment with clinical improvement. Later the culture was positive for M. tuberculosis.